Comparing accuracy of denture bases fabricated by injection molding, CAD/CAM milling, and rapid prototyping method - Lee, Suji; Hong, Seoung-Jin; Paek, Janghyun; Pae, Ahran; Kwon, Kung-Rock; Noh, Kwantae (The journal of advanced prosthodontics, 2019)
The accuracy of denture bases was compared among injection molding, milling, and rapid prototyping (RP) fabricating method. The maxillary edentulous master cast was fabricated and round shaped four notches were formed. The cast was duplicated to ten casts and scanned. In the injection molding method, designed denture bases were milled from a wax block and fabricated using SR Ivocap injection system. Denture bases were milled from a pre-polymerized block in the milling method. In the RP method, denture bases were printed and post-cured. The intaglio surface of the base was scanned and surface matching software was used to measure inaccuracy. Measurements were performed between four notches and two points in the mid-palatal suture to evaluate inaccuracy. The palatine rugae resolution was evaluated. One-way analysis of variance was used for statistical analysis at α=.05. No statistically significant differences in distances among four notches ( >.05). The accuracy of the injection molding method was lower than those of the other methods in two points of the mid-palatal suture significantly ( <.05). The degree of palatine rugae resolution was significantly higher in the injection molding method than that in other methods ( <.05). The overall accuracy of the denture base is higher in milling and RP method than the injection molding method. The degree of fine reproducibility is higher in the injection molding method than the milling or RP method.